Photocatalytic Reduction of Nitroaromatics Initiated by Bare/Metal-TiO2 Nanostructures - Kaur, Jaspreet (My University, 2015)
This thesis presents a fine approach into many aspects of Titanium dioxide (TiO2) nanomaterials and their applications for photocatalytic reduction of nitroaromatics. Bare and metal loaded TiO2 nanostructures viz., nanospheres and nanorods of different crystal phases viz., anatase and rutile have been synthesized to investigate the effect of size, shape, phase, nature of co-catalyst onto the change in absorbance, photoluminescence, relaxation lifetime and photocatalytic activity for the reduction of nitroaromatics. The present thesis is divided into five chapters: Chapter 1: Introduction, Preparation and Characterization Techniques The first chapter introduces the brief mechanism of TiO2 semiconductor photocatalysis, effect of metal loading onto TiO2, crystal phase, morphology, photoreduction of nitroaromatics with TiO2 and literature survey on TiO2 nanostructures with photocatalysis as an application point of view. Further, various techniques used for synthesis and characterization of bare and metal loaded TiO2 nanocomposites are discussed. TiO2 nanostructures of different morphologies viz.; nanospheres and nanorods as well different phase viz.; anatase and rutile have been synthesized by calcinations at temperature 400-800 ºC, hydrothermal, solvothermal and sol gel methods. Coinage and platinum group metals were deposited onto TiO2 surface by photodeposition techniques. The as synthesized materials have been characterized by diffused reflectance spectroscopy, photoluminescence; time resolved spectroscopy, transmission electron microscope, BET surface area analyzer and X-ray diffraction study. Photoreduction of nitroaromatics were conducted under UV light irradiations. Products and intermediates have been identified by high performance liquid chromatography, gas chromatography-mass spectroscopy, nuclear magnetic resonance spectroscopy and gas chromatography techniques. Chapter 2: 100% selective yield of m-nitroaniline by rutile TiO2 and m-phenylenediamine by P25-TiO2 during m-dinitrobenzene photoreduction The effect of rutile content, solvent, catalyst amount, irradiation time, crystallinity, surface area and electron withdrawing groups for selective photoreduction of m-dinitrobenzene have been discussed here. Photoreduction of m-dinitrobenzene (25 μmol) in the deaerated aqueous iso- propanol exhibits 100% selective yield of m-nitroaniline (25 μmol) by rutile TiO2 (50 mg) or m-phenylenediamine (25 μmol) by P25-TiO2 separately under 8 and 4 h of UV light irradiation (125 W Hg arc, 10.4 mW/cm2), respectively. It revealed that insertion of a second –NO2 group in nitrobenzene ring has an important role in expediting –NO2 reduction to –NH2 as compared to a negligible reduction of nitrobenzene under similar conditions, indicating that electron withdrawing groups lower the electron density on –NO2 present on meta position and favor quick reduction of the –NO2 group. Chapter 3: Influence of coinage and platinum group metal co-catalysis for the photocatalytic reduction of m-dinitrobenzene by P25 and rutile TiO2 In this chapter, the co-catalytic activity of 1 wt% coinage (Au, Ag and Cu) metals and platinum group (Pt, Pd and Rh) metals deposited P25 and rutile TiO2 (R-TiO2) have been relatively investigated for the optical absorption, emission, surface structural morphology and photocatalytic activity for the selective reduction of m-dinitrobenzene under UV light irradiation. An average particle size ~122 nm of R-TiO2 is increased after calcinations of P25-TiO2 (25-30 nm) at 800 °C and Au and Pt deposits of size ~4.0‒6.5 nm were found to be uniformly distributed over TiO2 surface. Although the optical band gap does not alter much, but intense photoluminescence having several characteristic bands between 400-550 nm are significantly quenched depending on the nature of metal loading. Photoirradiation (125 W Hg arc, 10.4 mWcm-2) of bare P25-TiO2 suspended in isopropanol (50 vol%) containing m-dinitrobenzene selectively produces 100% m-phenylenediamine, while metal deposited P25-TiO2 produces m-nitroaniline as a major product after 4 h of UV light irradiation. However, bare R-TiO2 produces 100% m-nitroaniline and metal loading does not alter the selectivity except the decrease in reduction efficiency of R-TiO2. The decrease in active Ti3+ sites available on the surface after metal loading might be responsible for the decrease in photocatalytic activity. Chapter 4: Selective formation of benzo[c]cinnoline by photocatalytic reduction of 2,2′- dinitrobiphenyl using TiO2 and under UV light irradiation This chapter demonstrates that the photocatalytic reduction of 2,2′-dinitrobiphenyl (DNBP, 25 μmol) in aqueous iso-propanol (50 vol%) and P25-TiO2 (50 mg) under argon atmosphere and 20 h of UV light irradiation selectively produced 23.8 μmol of benzo[c]cinnoline (BC, 95%), and 2,2′-biphenyldiamine (BPD, 5%) whose amount is gradually increased with irradiation time beyond 20-24 h due to further reduction of BC. It is also observed that the reduction process is accompanied by the simultaneous oxidation of iso-propanol (hole scavenger) to acetone whose amount is increased with (20 to 24 h) irradiation time, and no H2 production is detected by photoexcited holes (h+) in the valence band under UV irradiation. Furthermore, over oxidation of acetone into CO2 was not observed. It is evident that DNBP undergoes intramolecular reductive cyclization reactions by TiO2 because of the close spatial proximity of the interacting NO2 groups that lie in two different benzene rings separately relative to their location in a same benzene moiety in various dintirobenzene. Chapter 5: Crystal phase and shape dependent photoactivity of titania for nitroaromatics reduction under UV light irradiation This chapter describes importance of different shapes and crystal phases of TiO2 nanostructures such as RNP, RNR, ANP, ANR and P25-TiO2 (70:30 anatase and rutile) for the PCA for m-nitrotoluene (m-NT) and m-nitrobenzoic (m-NBA) photoreduction under UV light irradiation. RNR (L×W = 28-30 nm × 3.5-3.8 nm) showed superior photoactivity ( ̴ 3 times) as compared to RNP of size 122 nm for the photoreduction of m-NT into m-toluidine (m-TD) and m-NBA into m-aminobenzoic acid (m-ABA) under 8 h UV irradiation. The obtained results show that the long distance electron transport along longitudinal length, larger surface area (69 m2g-1), quenched PL emission, increased lifetime of charge carriers (1.8 ns) of RNR as compare to RNP having lower surface area (18 m2g-1) and charge carrier lifetime (1.1 ns) collectively contribute to its enhanced PCA. Furthermore, ANP of size 8-10 nm having surface area 89 m2g-1 also shows higher PCA than anatase nanorods of size (L×W = 80-132 nm × 8-13 nm and surface area = 71 m2g-1) and P25-TiO2 (25-30 nm) for m-NBA and m-NT photoreduction under 6 h UV light irradiation. The overall rate of reduction/hour for m-NBA and m-NT photoreduction with all of these catalysts has been found to vary in the following order ANP> P25-TiO2> RNR> ANR> RNP.
Ph.D. (SCBC)
Keywords: Nitroaromatics reduction; dinitrobenzene photoreduction; rutile TiO2; metal TiO2 photoactivity; chemistry and biochemistry